Divine Providence in the Joseph Narrative: A Narrative Theological Reading of Genesis 37-50 - Eni Lestari (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This article examines divine providence in the Joseph narrative of Genesis 37-50 through a narrative-theological reading. Previous scholarship has tended to treat this narrative in fragmentary ways, focusing on isolated episodes rather than on the text as a coherent literary whole, thereby obscuring its theological movement. Using a qualitative synchronic approach informed by biblical narrative criticism (Alter, Bar-Efrat, Fokkelman) and canonical-linguistic theology (Vanhoozer), this article reads Genesis 37-50 in its final form and analyzes its plot movement, recurring motifs, patterns of reversal, and retrospective theological speech. The study argues that divine providence in the Joseph narrative is disclosed not primarily through overt miracle, but through hidden yet effective divine governance working through suffering, betrayal, slavery, imprisonment, political elevation, and reconciliation. Particular attention is given to Genesis 50:20 as the theological climax of the narrative, where human evil and divine intention are held together without collapsing moral responsibility. The findings demonstrate that the Joseph story presents providence as God's governance of history toward the preservation of life, a governance that is narratively grounded, ethically serious, and irreducible to personal success or doctrinal formula. This reading contributes to Biblical Studies by offering an integrated account of providence across the whole Joseph narrative, one that holds literary shape and theological claim within a single interpretive frame.